Almost 30 : a definitive guide to a life you love for the next decade and beyond - Simcik, Lindsey; Williams, Krista (Podcaster) (St. Martin's Essentials, 2025)
"Go from lost to a life you love and make your thirties your best decade yet with this inspiring, hilarious, and vulnerable book from creators of the #1 critically acclaimed podcast, Almost 30. The years leading up to 30 can feel more agonizing than exciting. The pressure to have it all figured out-your job, your relationship, your LIFE-is intense. And as if that's not enough, bam! Along comes Saturn Return, a cosmic milestone that thrusts you into adulthood ... ready or not. Yes, it can all feel overwhelming, and the fear of the unknown is real. While part of you might want to cling to the status quo (whether it's actually working for you or not), there is another, more powerful part of you that won't allow that to happen. This book is here to talk to that part of you. Lindsey Simcik and Krista Williams-creators of the #1, critically acclaimed wellness podcast and global community Almost 30-help you navigate this season of astronomical (and astrological) transition in your life. Consider them the big sisters of your Saturn Return, here to guide you, hold your hand, and cheer you on as you embark upon this monumental transition that will touch every single part of your life, from your body to your relationships to your spirituality. In addition to looking back at their own alternately hilarious and insightful experiences of being almost thirty, this book contains the expert insights, research, practices, and tools they've cultivated through nearly a decade of hosting Almost 30. Dive into thought exercises, meditations, journaling prompts, and sage advice from expert podcast guests such as Jay Shetty, Gabrielle Bernstein, Glennon Doyle, Nicole LaPera, and many more. Almost 30 is the go-to book for every woman standing on the cusp of where they've been and where they're going. Because change is imminent, and we're all almost ... something"--